2015
DOI: 10.6066/jtip.2015.26.1.17
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Marination Time on the Quality of Traditional Dried Meat Ready to Eat

Abstract: Generally, marination time at home industry of dried meat "jerky" in NTB province was conducted up to 18 hours at room temperature, which promote the growth of foodborne pathogen. This research was aimed to determine the effective and efficient marination time to produce a good quality of jerky. A previous study showed that 2.5% of liquid smoke Grade 1 was recommended to be used in traditional jerky processing. Therefore, the concentration was used for marination of sliced meat in traditional spices for 0, 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…further research by Pursudarsono et al, (2015) stated that, the pH value in foodstuffs that were given sugar 20% (5.75±0.08), sugar 30% (5.77±0.19), sugar 40% ( 5.90 ± 0.06) and high sugar content along with low acid content can increase the shelf life of foodstuffs. Handayani et al, (2015) stated that the pH value of chicken meat jerky in the home industry is 5.85 on average. It can be concluded that the results of the study of chicken jerky that received treatment with a sugar concentration of 40% were the best because they were close to the pH value of chicken meat jerky products on a household scale.…”
Section: Phmentioning
confidence: 99%
“…further research by Pursudarsono et al, (2015) stated that, the pH value in foodstuffs that were given sugar 20% (5.75±0.08), sugar 30% (5.77±0.19), sugar 40% ( 5.90 ± 0.06) and high sugar content along with low acid content can increase the shelf life of foodstuffs. Handayani et al, (2015) stated that the pH value of chicken meat jerky in the home industry is 5.85 on average. It can be concluded that the results of the study of chicken jerky that received treatment with a sugar concentration of 40% were the best because they were close to the pH value of chicken meat jerky products on a household scale.…”
Section: Phmentioning
confidence: 99%